Constructing "Kin" Citizens: An Investigation of Canadian Kinesiology Programs' Mission and Vision Statements. Issue 4 (2nd October 2022) - Barnes, Sarah; Nakamura, Yuka; Safai, Parissa
ABSTRACT: The purpose of this article is to explore how social forces related to the corporatization of universities play out at the granular level of institutional mission and vision statements in the racialized context of Canadian Kinesiology. The stated aims of Canadian Kinesiology academic units (N = 36) were collected from their public-facing websites, and we conducted a critical discourses analysis of our evidence. We argue that mission and vision statements construct Kinesiology as an altruistic and impactful scholarly project and conceal the contested nature of health, scientific knowledge, and community engagement in the field. Careful analysis of the data, with particular attention paid to that which is unspoken, silenced or erased, highlights how these guiding declarations can renew the field's underlying racial and colonial logics. To conclude, we note instances when programs use institutional statements to unsettle dominant scripts and open possibilities to work toward a more progressive and just Kinesiology.